Definición y caracterización de la evaluación colegiada en los procesos artístico-pedagógicos de la licenciatura en educación artística con énfasis en danza y teatro de la facultad de educación de la Universidad Antonio Nariño. (2018)
The main objective of this work is to approach the definition and characterization of the collegiate evaluation in the disciplinary and complementary courses of dance, theater, make-up, music, drawing and theory, each one of which is part of the integral elements that constitute the graduate student of the Program: Degree in artistic education with an emphasis in dance and theater from the faculty of education of the Antonio Nariño University, in the process of change of denomination. Degree in Performing Arts. In order to achieve the above, it was necessary to use information sources such as research from other universities, interviews, stories, surveys of teachers, graduates and students of the program.